Former Yugoslav Republic of Macedonia : Technical Assistance Evaluation Report. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses findings of the Technical Assistance Evaluation Report for the former Yugoslav Republic of Macedonia. Overall, the authorities indicated that technical assistance (TA) and training had been very useful in improving its statistical systems and statistics. The approach to provide subject-specific TA following the Data Module Report on the Observance of Standards and Codes (ROSC) was effective as the ROSC assessment was helpful in setting the context for future TA. The authorities emphasized the usefulness of training. They noted that despite the slow pace of implementation of TA missions' recommendations in some cases, training had contributed to their understanding of international standards.